UV SPECTROPHOTOMETRIC ANALYSIS AND VALIDATION OF ACYCLOVIR IN SOLID DOSAGE FORM - LASURE, AKSHATA; ANSARI, AFAQUE; KALSHETTI, MALLINATH (International Journal of Current Pharmaceutical Research, 2020)
Objective: A new, economical, sensitive, simple, rapid UV spectrophotometric method has been developed for the estimation of Acyclovir in pure form and pharmaceutical formulation. Methods: This UV method was developed using distilled water as a solvent. In the present method, the wavelength selected for analysis was 254 nm. UV-Visible double beam spectrophotometer (Systronic 2201) was used to carry out the spectral analysis. The ICH guidelines were used to validate the method. Results: The method was validated for linearity, range, accuracy, precision, robustness, LOD and LOQ. Linearity was found in the range of 5-30µg/ml. Accuracy was performed by using a recovery study. The amount of drug recovered was found to be in the range of 100.1-100.5 %. The % RSD value was found to be less than 2. Conclusion: The proposed UV spectroscopic method was found to be accurate, precise, stable, linear, specific, and simple for quantitative estimation of acyclovir in bulk and pharmaceutical dosage form. Hence the present UV spectroscopic method is suitable for the routine assay of acyclovir in bulk and pharmaceutical formulations.